2022
DOI: 10.1021/acsami.2c00793
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Titanium Oxide Nanowire Film: a Multifunctional Solar Energy Utilization Platform for High-Salinity Organic Sewage Treatment

Abstract: The treatment of high salt organic sewage is considered to be a high energy consumption process, and it is difficult to degrade organic matter and separate salt and water simultaneously. In this study, a gradient structure titanium oxide nanowire film is developed, which can realize the thorough treatment of sewage under sunlight. Among the film, part TiO2–x has enhanced photocatalytic properties and can completely degrade 0.02 g·L–1 methylene blue in 90 min under 2 sun. Part Ti n O2n–1 has excellent photothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…DOM stability and dynamics are very important for environmental pollution and soil organic carbon storage. ,, Studies have shown that noncrystalline minerals in soil control soil organic carbon sequestration . Therefore, it is necessary to study the complex interaction between DOM and noncrystalline minerals.…”
Section: Discussionmentioning
confidence: 99%
“…DOM stability and dynamics are very important for environmental pollution and soil organic carbon storage. ,, Studies have shown that noncrystalline minerals in soil control soil organic carbon sequestration . Therefore, it is necessary to study the complex interaction between DOM and noncrystalline minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, Yan et al prepared graphene‐based hybrid aerogel, exhibiting the evaporation rate of 2.1 kg m −2 h −1 as well as the phenol degradation efficiency of 95% 18 . Si et al developed gradient structure titanium oxide nanowire, which achieved the evaporation rate of 1.83 kg m −2 h −1 and high removal efficiency of methylene blue 19 . Zhang et al prepared MXene hydrogel, exhibiting the water evaporation rate of 1.82 kg m −2 h −1 with high Rhodamine B degradation efficiency (90.5%) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Si et al developed gradient structure titanium oxide nanowire, which achieved the evaporation rate of 1.83 kg m À2 h À1 and high removal efficiency of methylene blue. 19 Zhang et al prepared MXene hydrogel, exhibiting the water evaporation rate of 1.82 kg m À2 h À1 with high Rhodamine B degradation efficiency (90.5%). 20 In spite of the outstanding achievement, these devisable structures usually contain either costly materials or complex preparation processes, which impede their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the ZCP-20 membrane exhibits a high evaporation rate of 2.48 kg m À2 h À1 under one sun irradiation and displays stable evaporation rates for 20 h. Remarkably, the ZCP-20 membrane can tolerate various water sources (e.g., dye-polluted water) or even strongly acidic (pH = 1) or basic (pH = 13) solutions.With rapid population growth and extensive water pollution, the demand for freshwater resources has increased sharply. [1][2][3][4][5] Solar-thermal steam generation is an energy-efficient water purification technology potentially capable of alleviating the fresh water shortages, which has been widely investigated for producing freshwater from seawater or sewage. [6][7][8][9][10] In order to enhance the water evaporation performance of functional materials, enormous attempts have been devoted to controlling their morphology by creating hierarchical architectures, [11][12][13] including carbon-based materials, 14-16 metals, 17,18 metal oxides/carbides, 19,20 polymers, [21][22][23] and porous frameworks.…”
mentioning
confidence: 99%
“…With rapid population growth and extensive water pollution, the demand for freshwater resources has increased sharply. 1–5 Solar-thermal steam generation is an energy-efficient water purification technology potentially capable of alleviating the fresh water shortages, which has been widely investigated for producing freshwater from seawater or sewage. 6–10 In order to enhance the water evaporation performance of functional materials, enormous attempts have been devoted to controlling their morphology by creating hierarchical architectures, 11–13 including carbon-based materials, 14–16 metals, 17,18 metal oxides/carbides, 19,20 polymers, 21–23 and porous frameworks.…”
mentioning
confidence: 99%